The effect of the coefficient of friction between the roller and the powder on the rolling process. Issue 1 (1st December 2022) - Yin, Quan-zhong; Li, Xiao-qiang; Liang, Yong-ren; Li, Rong; Ren, Shang-yuan; Kang, Zhi-Xin
Abstract: The friction coefficient between the roller and the powder is one of the important factors affecting the rolling process. Since the friction coefficient is difficult to measure during rolling, it is usually regarded as a constant value in previous studies. However, the friction coefficient changes with the changes in process parameters such as the gap size and the rolling speed. In order to study the effect of the friction coefficient between the roller and the powder on powder rolling, the Drucker Prager Cap model for nickel powder rolling was established by ABAQUS. Firstly, the changes of contact stress (CPRESS) between the roller and the powder, the width (PE33), and relative density (SDV1) of the strip during rolling were analyzed. Then, the effect of the friction coefficient between the roller and the powder on the contact stress, the width, and the relative density of the strip was studied especially. The results show that during the rolling process, the contact stress remains basically unchanged. However, a large transverse deformation occurs on both sides of the strip, and the deformation in the middle is basically small. The relative density is greatest at the smallest seam between the rollers, and it decreases slightly after moving away from the roller, and then it remains stable. The coefficient of friction between the roller and the powder has an impact on the rolling result, in which the contact stress between the roller and the powder, the width, and the relative density of the strip will increase as the friction coefficient increases.